Strong flux pinning at 4.2 K in SmBa2Cu3Oy coated conductors with BaHfO3 nanorods controlled by low growth temperature. (11th July 2017) - Miura, S; Tsuchiya, Y; Yoshida, Y; Ichino, Y; Awaji, S; Matsumoto, K; Ibi, A; Izumi, T
Abstract: In order to apply REBa2 Cu3 O y (REBCO, RE = rare earth elements or Y) coated conductors in high magnetic field, coil-based applications, the isotropic improvement of their critical current performance with respect to the directions of the magnetic field under these operating conditions is required. Most applications operate at temperatures lower than 50 K and magnetic fields over 2 T. In this study, the improvement of critical current density ( J c ) performance for various applied magnetic field directions was achieved by controlling the nanostructure of the BaHfO3 (BHO)-doped SmBa2 Cu3 O y (SmBCO) films on metallic substrates. The corresponding minimum J c value of the films at 40 K under an applied 3 T field was 5.2 MA cm −2, which is over ten times higher than that of a fully optimized Nb–Ti wire at 4.2 K. At 4.2 K, under a 17.5 T field, a flux pinning force density of 1.4 TN m −3 for B // c was realized; this value is among the highest values reported for REBCO films to date. More importantly, the F p for B // c corresponds to the minimum value for various applied magnetic field directions. We investigated the dominant flux pinning centers of films at 4.2 K using the anisotropic scaling approach based on the effective mass model. The dominant flux pinning centers are random pinning centers at 4.2 K, i.e., a high pinning performance was achieved by the high number density of random pins in the matrix of the BHO-doped SmBCO films.